Variações genéticas da glicoproteína B do citomegalovírus humano e associação com o nível de citocinas em pacientes submetidos ao transplante alogênico de células tronco hematopoiéticas - Jeane de Fatima Correia Silva (2010)
Introduction: Factors as human cytomegalovirus (HCMV) load, recipient/donor histocompatibility, patient/donor gender, recipient age, graft-versus-host disease (GVHD) and cytokine levels have been considered important prognostic parameters in allogeneic hematopoietic stem cell transplantation (allo-HSCT). Glycoprotein B (gB) protein has proved to be important in HCMV infectivity and in eliciting a immune response in patients with HCMV infection. The immunological components associated with HCMV control are not completely understood. Objective: The aims of the present study were to assess the prevalence of the gB genotypes in patients who underwent allo-HSCT and to investigate the possible relationship between these genotypes and IL-1, IL-6, IL-10, IFN- and TNF- levels in saliva and blood samples. In addition, we evaluated the impact of the gB genotype, cytokines levels and other risk factors on patients survival. Thus, to investigate the impact of IL-1, IL-6, IL-10, IFN- and TNF- levels, HCMV load in saliva and blood in recipients survival Methods: Saliva and blood samples were sampled weekly in 63 allo-HSCT patients until 100 days after transplant. HCMV gB genotyping was carried out by multiplex nested PCR. The cytokines levels were assessed by ELISA and HCMV load was determined by real time PCR assay. Results: Thirty six of 63 saliva samples and 52 of 63 blood samples were negative to gB HCMV genotype. gB2 was the most common genotype in saliva (19/36) and blood (33/52). Patients with gB2 in saliva showed lower IL-10 salivary levels in comparison with patients without this genotype (p=0.023). Reduced blood levels of IFN- (p=0.040) and IL-1 (p=0.050) were also found in recipients presenting the HCMV gB4 genotype comparing patients without it. Recipient gender, combination patient/donor gender, stem cell source and aGVHD presented impact in allo-HSCT survival. High levels of IL-6 in saliva and low levels of IFN- in blood seven days before allo-HSCT were associated with increased risk of death. High levels of IL-6 in blood and high HCMV load in saliva 21 days after allo-HSCT decrease the recipient survival. Conclusions: The gB2 genotype is the most prevalent gB HCMV genotype in saliva and blood of patients who underwent allo-HSCT. Despite an association between blood and saliva cytokine levels in patients with different gB genotypes and also with survival, HCMV gB genotypes have no impact on patient outcome. The increased IL-6 level and HCMV load in saliva, the increased IL-6 level and decreased IFN- level in blood are associated with a worst survival rate. These findings suggest a potential function for these markers in determination of allo-HSCT survival. Further studies are necessary to investigate the function of salivary IL-6 as a potential biomarker of allo-HSCT survival and its possible association with salivary HCMV load.